AKTIFITAS ENZIM SALURAN PENCERNAAN IKAN NILA (OREOHROMIS NILOTICUS) DENGAN PAKAN MENGANDUNG TEPUNG DAUN LAMTORO (LEUCAENA LEUCOPHALA) TERHIDROLISIS DAN TANPA HIDROLISIS DENGAN EKSTRAK ENZIM CAIRAN RUMEN DOMBA - Indira Fitriliyani (Universitas Lambung Mangkurat, 2011)
This experiment was conducted to compare digestive enzyme activity of of nile tilafia with feed formulation contain Hydrolyzed and non Hydrolyzed Leucana leucophala Leaf Meal with Sheep Rumen Liquor Enzyme Extract. Fish were fed isonitrogenous (± 32% crude protein and C/P ± 9,25 kkal/kg) diets for 50 days in 18 aquarium with a recirculation water system. 12 diets were formulated to contain hydrolyzed LLM and non hydrolyzed LLM at level 10% 15% 20% 25% and 30% and one diet acting as a control (0% LLM). All diets were isonitrogenous and isoenergy. A seven week feeding trial was carried out on triplicate groups of eight fish (9.38 ± 0,41) in 36 aquarium with a recirculating system. Fish were fed twice daily as satiation. Results of the present study indicate that using hydrolyzed LLMin fed formulation can be incrase protease, amilase and cellulase enzyme activity in digestive tract nile tilapia.